Using Fairy Tales in English Lessons in Primary School - Abdukhafizov Firdavs (International Journal on Human-Computing Studies, 2023)
This article discusses the features of teaching a foreign language in primary school using fairy tales of an international character as didactic material. Studying fairy tales in English lessons helps to combine elements of literary and linguistic analysis. The introduction of a fairy tale into a foreign language lesson makes it possible to analyze various types of speech activities that should be practiced in English lessons.